Biosynthesis of silver nanoparticles with antibacterial, antioxidant, anti-inflammatory properties and their burn wound healing efficacy - Bold, Bum-Erdene; Urnukhsaikhan, Enerelt; Mishig-Ochir, Tsogbadrakh (Frontiers in Chemistry, 2022)
The current study aims to develop a novel burn wound ointment consisting of sheep’s tail ointment loaded with AgNP. The AgNP in the ointment serves as an antibacterial, antioxidant and anti-inflammatory agent. The AgNP was developed via the biological method with the assistance of the medicinal plant Rhodiola rosea. The characterization of AgNP was assessed using UV-Vis spectroscopy, FTIR, Zeta Potential, XRD, PCCS, SEM, and EDX techniques. The formation of AgNP was confirmed by UV-Vis spectrum at the absorbance of ~430 nm, and the biomolecules responsible for reducing and capping the AgNP were characterized by FTIR analysis. The stability of AgNP was determined with Zeta potential, which revealed a highly stable colloidal solution with a surface charge of -68.38±3.4 mV. The synthesized AgNP had a face-centered cubic structure with a crystallite size of 23 nm and average grain size of 67.5 nm. The SEM image showed a fairly monodisperse 20 nm-sized spherical-shaped AgNP. The synthesized AgNP contained high purity of the silver, and a low concentration of AgNP inhibited both Gram-positive and Gram-negative bacteria. Moreover, the scavenging activity of AgNP was investigated using DPPH and H2O2 scavenging assay, and the results revealed a dose-dependent antioxidant activity with the highest activity at a concentration of 450 µg/ml. Finally, the burn wound healing effect was evaluated by applying the AgNP-loaded ointment to the wound site of BALB/c mice. The in-vivo studies confirmed that AgNP-loaded ointment reduced the wound size, decreased the epidermis layer, and lowered mast cell migration compared to untreated burn wounds. And the synthesized AgNP regulated both pro-inflammatory and anti-inflammatory gene expression, thereby promoting burn wound closure on BALB/c mice. The developed AgNP-loaded ointment has the potential to be applied in the biomedical field.